Efficient capture of Sr2+ from acidic aqueous solution by an 18-crown-6-ether-based metal organic framework. Issue 18 (20th April 2021) - Guo, Chenglong; Yuan, Mengjia; He, Linwei; Cheng, Liwei; Wang, Xia; Shen, Nannan; Ma, Fuyin; Huang, Guolin; Wang, Shuao
Abstract : Here, Guo et al. report a metal organic framework material (SNU-200) functionalized with an 18-crown-6-ether, whose specific binding site with an excellent affinity toward strontium leads to excellent Sr 2+ adsorption capability under acidic conditions at low concentrations. Abstract : The capture of highly radiotoxic 90 Sr from an acidic waste solution during used fuel reprocessing and environmental remediation in a nuclear accident is desirable and challenging. Herein, we show a metal organic framework material (SNU-200) functionalized with an 18-crown-6-ether, whose specific binding site with an excellent affinity toward strontium leads to excellent Sr 2+ adsorption capability under acidic conditions. This material exhibits a high adsorption capacity (44.37 mg g −1 at pH = 3), remarkable affinity ( K d = 3.63 × 10 4 mL g −1 ) and ultrahigh selectivity in the presence of interfering coexisting ions such as Na +, K +, Cs +, Mg 2+, and Ca 2+ .